The Effectiveness of the Native Training Model Designed Based on Lazarus Theory and Behavioral Planning Theory in the Consolidation of Family Functioning: A case study - Jallal Iranizadeh; Hassan Zarei Mahmoodabadi; Saeed Vaziri; Seyed Alireza Afshani (Shahid Sadoughi University of Medical Sciences, 2020)
Abstract Introduction: Recently, consolidation of family functioning is considered as one of the most important solutions for elevating and strengthening marital life. Therefore, benefiting from family strengthening approaches is so truly significant. This research aims at investigating the effectiveness of the native model based on Lazarus theory and behavioral planning theory on the consolidation of family functioning. Method: This research is a quasi-experimental study with a pretest-posttest design and control group. The population includes all the couples referring to counseling and psychotherapy centers of Yazd Province, in Iran, 2019. Purposive sampling was used to select 34 couples who have the inclusion criteria, and they were randomly assigned to experimental and control groups. The couples answered the family consolidation questionnaire designed by Movahed et al. The experimental group received 11 sessions of interventions extracted from the localized Lazarus model and behavioral planning theory. Finally, data analysis was done by SPSS version 16 and an analysis of covariance (ANCOVA). The significance level of research was considered to be α=0.05 Findings: The results showed that there is a significant difference between the estimated mean score of the family consolidation in the experimental and control groups. Also, the findings suggest that compared with the control group, the posttest scores of the performance, problem-solving, relationship, emotional involvement, emotional support, role play, behavioral control, media, and superstition have been improved in the experimental group. This significant difference results from the training intervention. However, the variable of religious beliefs has not changed significantly. Conclusion: The training intervention done by the model has developed based on Lazarus theory and behavioral planning theory which can consolidate the family functioning.